The seagull eaudiobook - Cleeves, Ann (Vera Stanhope, 2017)
"Janine Birkett's marvelous narration enhances this riveting mystery, part of the Vera Stanhope series, set on the majestic northeast coast of England...Listeners will appreciate Birkett's handling of the dry humor, particularly Stanhope's" — AudioFile Magazine From Ann Cleeves— New York Times bestselling and award-winning author of the Vera and Shetland series, both of which are hit TV shows—comes The Seagull . A visit to her local prison brings DI Vera Stanhope face to face with an old enemy: former detective superintendent, and now inmate, John Brace. Brace was convicted of corruption and involvement in the death of a gamekeeper – and Vera played a key part in his downfall. Now, Brace promises Vera information about the disappearance of Robbie Marshall, a notorious wheeler-dealer who disappeared in the mid-nineties, if she will look out for his daughter and grandchildren. He tells her that Marshall is dead, and that his body is buried close to St Mary's Island in Whitley Bay. However, when a search team investigates, officers find not one skeleton, but two. This cold case case takes Vera back in time, and very close to home, as Brace and Marshall, along with a mysterious stranger known only as 'the Prof', were close friends of Hector, her father. Together, they were the 'Gang of Four', regulars at a glamorous nightclub called The Seagull. Hector had been one of the last people to see Marshall alive. As the past begins to collide dangerously with the present, Vera confronts her prejudices and unwanted memories to dig out the truth . . . The Seagull is a searing novel by Sunday Times bestselling author Ann Cleeves, about corruption deep in the heart of a community, and fragile, and fracturing, family relationships. "Definitely one of the best crime novels of 2017."—Reviewing the Evidence